Spreadsheet-based modelling for out of matrix cost in inbound logistics. (2017) - Shah, Mrinalini; Daga, Mayank Kumar
The purpose of the study was to estimate non-budgeted cost incurred by an FMCG company in its inbound logistics operations for a selected product category. We conducted the study through action research approach, and collected primary data for all its shipment made from all the manufacturing units of the company to its distributors across PAN India. A quantitative model was developed to estimate the logistics cost for six-month period and a spreadsheet-based model was designed to generate reports to provide ease of use to decision makers/managers. The study identified the lack of coherence in logistics planning and implementation stage, resulting in excess than the budgeted expenditure. The present research indicated that the out-of-matrix cost constituted an average 25% of the total transportation cost for the study period. We identified the potential causes for such inefficiencies and recommended to use developed model in getting a more realistic scenario through the developed model.